Assessing resilience in tourism: The case of Greece - Stella Karoulia; Eleni Gaki; Stella Kostopoulou (European Regional Science Association (ERSA), 2015)
During the last decade a new concept has emerged in the regional science debate, the notion of regional resilience, defined as the ability of a region to prevent, prepare, respond and recover after a disturbance, in order that this disturbance does not stand as an obstacle to the regions development. Regional resilience is characterized by the capacity of a regional economy to i) withstand external pressures, ii) to respond positively to external changes and iii) to adjust and to learn. According to the international literature, a region should exhibit certain characteristics in order to be considered as resilient, including resourcefulness, performance, redundancy, diversity, innovative learning, connectedness, robustness and rapidity. The aim of this paper is to explore the notion of resilience in the tourism industry. Tourism, an important economic activity and fast growing industry worldwide, is one of the main income ‎sources for many countries, including Greece. In Greece, tourism represents over 17% of the country's GNP and 18,3% of total employment. During the years of recent economic crisis, the Greek tourism sector has been affected less than other economic activities, indicating its importance for the Greek economy. Nevertheless, significant variations in the resilience of tourism on economic crisis impact seem to have occurred among regions and therefore research regarding regional tourism resilience has grown in importance. This paper aims to investigate the extent to which Greek regions are resilient as far as tourism industry is concerned. More specifically, we valuate the adaptability of regions, tourism destinations and actors to the socio-economic changes and the degree of resilience of each region during the economic crisis i.e. whether they can cope with it, overcome it and recover from it. Furthermore, we intend to investigate how the evaluation of present resilience can contribute to the improvement of resilience planning and management on a regional basis. The central thesis of this research is that regional variations in the tourism industry resilience call for regionally adjusted tourism planning and management policies. In order to achieve the aim of the research, we will examine the impact of economic crisis on regional hospitality industry employment, measured by the change in the number of jobs in hospitality business (hotels) within each region, and attempt to model employment resilience after the industry experiences an economic shock. Tourism industry is a critical source of regional economic activity, and therefore it is important to understand what happens to industry employment due to economic crisis and the mechanisms by which regional tourism industry resilience is achieved. In this way, we will investigate the impact of the socio-economic changes in regions and through the noted declinations we will estimate the extent to which these regions are tourism resilient in economic shocks.
Keywords: R11; 330; resilience; tourism; economic crisis; regions; Greece